UPAYA PENINGKATAN KEMAMPUAN SISWA KELAS X PROGRAM KEAHLIAN TEKNIK BANGUNAN DENGAN MODEL TUTOR SEBAYA (PEER TUTORING) PADA MATA PELAJARAN GAMBAR TEKNIK DI SMK N 5 SURAKARTA - Qusnul Angga Rosita; A G Thamrin; Chundakus Habsya (Universitas Sebelas Maret, 2015)
The purpose of this study was to determine: (1) Improving student learning outcomes in subjects Engineering Drawing by using Peer Tutoring learning model in class X Civil Engineering Program in SMK N 5 Surakarta. (2) The effectiveness of the application of the Peer Tutoring learning model in subjects Engineering Drawing in class X Civil Engineering Program SMK N 5 Surakarta cici4d. This study is a classroom action research conducted in class X Civil Engineering Program in SMK N 5 Surakarta with 31 students. This study was conducted in two cycles. Each cycle consists of a phase of implementation, observation and reflection. The instrument used in this study consisted of a test of learning outcomes and assessment sheets of observation. Test the data validity by using member check and analyze data by using interactive analysis, which consists of: data reduction, data presentation, drawing conclusions or verification cici4d. The results research with Peer Tutoring model indicate improvement of cognitive is 15.49%; psychomotor domains is 20.26%; affective is 20%; and effectiveness of learning increased up to 8.52%. Key word : Peer Tutoring, Learning outcomes, and Effectiveness